2010
DOI: 10.1007/s00228-010-0850-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYP2D6 and ABCB1 pharmacogenetics in drug-naïve patients with first-episode schizophrenia treated with risperidone

Abstract: 2 AbstractPurpose: To evaluate the role of cytochrome 450 2D6 (CYP2D6) and ABCB1 variants on plasma risperidone concentrations and treatment response in 83 drug naive patients with first episode of psychosis.Methods: All patients were treated with risperidone for 8 weeks. The CYP2D6 genotyping was performed by allele-specific PCR-RFLP (for *3,*4,*6) and long PCR (for duplications and *5), while real-time PCR method was used for ABCB1 G2677T/A and C3435T. Plasma concentrations of risperidone and 9-OH risperidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 30 publications
(30 reference statements)
8
64
1
3
Order By: Relevance
“…For CYP1A2, the *1F polymorphism has been associated with poorer treatment response to clozapine and olanzapine. [24][25][26] One other study 27 [29][30][31][32] There are more data available indicating an impact of CYP polymorphisms on side effects: CYP2D6*3, CYP2D6*4, and CYP2D6*10, but not CYP1A2*1F, have been associated with increased AIWG. 24,33,34 Today, most evidence exists for an influence of CYP polymorphisms on motor adverse effects of APs, such as TD.…”
mentioning
confidence: 99%
“…For CYP1A2, the *1F polymorphism has been associated with poorer treatment response to clozapine and olanzapine. [24][25][26] One other study 27 [29][30][31][32] There are more data available indicating an impact of CYP polymorphisms on side effects: CYP2D6*3, CYP2D6*4, and CYP2D6*10, but not CYP1A2*1F, have been associated with increased AIWG. 24,33,34 Today, most evidence exists for an influence of CYP polymorphisms on motor adverse effects of APs, such as TD.…”
mentioning
confidence: 99%
“…Некоторые авторы [56] не нашли ассоциации между полиморфизмом С3435Т MDR1 и развитием позд-ней дискинезии, другие исследователи [58] продемон-стрировали положительные результаты. Проводились также исследования относительно риска развития острых экстрапирамидных расстройств: в одних работах [59] была ЖУРНАЛ НЕВРОЛОГИИ И ПСИХИАТРИИ, 4,2015 ОБЗОРЫ установлена связь полиморфизмов MDR1 и экстрапира-мидных нарушений, в других [60] -был получен отрица-тельный результат. В целом необходимы дальнейшие ис-следования, чтобы оценить роль полиморфизмов MDR1 в возникновении побочных эффектов.…”
Section: генетическая изменчивость генов системы транспортеров гематоunclassified
“…Three other studies involving healthy volunteers reported an indirect association between the PM or IM CYP2D6 phenotypes and a greater risk of developing EPS [126,127,128]. Finally, 2 studies involving risperidone-treated samples found no association between CYP2D6 metabolizer status and EPS [130,131]. …”
Section: Eps and Tdmentioning
confidence: 99%
“…Numerous studies published prior to 2010 have examined the relationship between CYP2D6 and EPS/TD, with the majority having supported a significant association between CYP2D6 metabolizer status and susceptibility to EPS/TD [121,122,123]. Eight studies published since 2010 have been reviewed here [124,125,126,127,128,129,130,131]. …”
Section: Eps and Tdmentioning
confidence: 99%